Analysis of angle measurements and a new approach to vertical angle calibation - Šiaudinytė, Lauryna; Rybokas, Mindaugas; Giniotis, Vytautas (Geodesy and Cartography, 2012)
Testing and calibrating geodetic instruments is an important metrological procedure for precise instrumentation used in industry and geodesy. Electronic geodetic measuring instruments consist, among other elements, of circular scales and angular encoders for angle determination in two perpendicular horizontal and vertical planes. The accuracy of the instrument mostly depends on the accuracy of angle standards used for angle calibration in the horizontal plane. Although many methods are developed for angle calibration, the majority of those are not available for calibrating angles in the vertical plane. The method described in the International Standards of vertical angle calibration validates field testing geodetic instruments by taking precise angle readings between the calibrated points placed at long distance and height. Difficulties in creating such calibration basis and inconveniencies in proceeding with this field at long distances may appear. Also, the traceability of length and angle measurements is not ensured. The new method of calibrating the angles in the vertical plane for geodetic instruments was developed. The article describes the principle of indoor testing and the calibration of the vertical angle measuring system. Vertikaliųjų kampų kalibravimo analizė ir nauji kalibravimobūdai Santrauka. Daugelyje optinių elektroninių matavimo prietaisų yra įmontuotos apskritiminės skalės, skirtos kampinei padėčiai dviejose statmenose plokštumose – horizontaliojoje bei vertikaliojoje nustatyti. Prietaiso tikslumas daugiausia priklauso nuo sių skalių tikslumo. Rastrinių skalių metrologija yra gana specifinė sritis, būtina tam tikra metodika ir kalibravimo įranga. Trumpai apžvelgus pateikiami kai kurie būdai ir priemonės, taikytini kampų metrologijai, ypač vertikaliam plokščiajam kampui kalibruoti. Reikšminiai žodižiai: geodezinis prietaisas, patikra, kalibravimas, rastrinė skalė. Aнaлиз углoвых измерений и новыe мeтoды калибрирoвания Резюме. Многие оптико-электронные измерительные инструменты состоят из круговых шкал для определения углов в двух перпендикулярных плоскостях – горизонтальной и вертикальной. Точность инструмента в основном зависит от точности этих угломерных шкал. Метрология угловых растровыx шкал довольно специфична и требует специфических мeтодов и приспособлений для калибрирования. В статье приводится обзор и некоторые простые способы и приспособления, которые можно использовать в метрологии углов, в частности, в калибрировании вертикального плоского угла. Ключевые слова: геодезический инструмент, сверка, калибрирование, растровая шкала.